O-035 Variability in clopidogrel response and associated perioperative thromboembolic and hemorrhagic complications in the initial cohort of patients treated with the pipeline device at a tertiary referral medical center. (4th July 2012) - Almandoz, J Delgado; Crandall, B; Scholz, J; Fease, J; Kadkhodayan, Y; Anderson, R; Tubman, D
Abstract : Purpose: To determine the variability in clopidogrel response and examine its relationship to perioperative thromboembolic and hemorrhagic complications in the initial cohort of patients treated with the Pipeline device at a tertiary medical center. Methods: The Abstract O-035 table 1 summarizes the dual antiplatelet therapy regimens implemented in the first 6 and subsequent 15 patients in our cohort. All patients underwent P2Y12 inhibition testing with the VerifyNow test. P2Y12 inhibition target therapeutic range was 40–199 platelet reaction units (PRUs) or 40-89% inhibition. Variability in patient response to clopidogrel therapy was defined as follows: (1) Non-responder if PRUs >240 or <20% inhibition, (2) poor responder if PRUs 200–240 or 20%–39% inhibition, (3) hyper-responder if PRUs <40 or ≥90% inhibition. Perioperative thromboembolic and hemorrhagic complications were recorded. Results: 21 patients were included in our study, 17 females (81%) and four males (19%). Mean patient age was 59.7 years (median 63 years, range 31–81 years). In the initial pre-treatment P2Y12 inhibition test, three patients were non-responders to clopidogrel therapy (14.3%), two patients were poor responders to clopidogrel therapy (9.5%), and two patients were hyper-responders to clopidogrel therapy (9.5%). In the post-treatment P2Y12 inhibition test, two patients who had initially been within the target therapeutic range became hyper-responders to clopidogrel therapy (9.5%, both symptomatic). Three patients experienced perioperative thromboembolic complications (14.3%, two cerebral infarctions and one transient ischemic attack), which resolved without a new permanent neurological deficit in two patients and caused a new permanent neurological deficit leading to moderate disability in one patient (4.8%). One patient experienced a perioperative hemorrhagic complication consisting of a frontal intracerebral hemorrhage ipsilateral to the Pipeline device (4.8%), which resolved without a new permanent neurological deficit. Two of the three patients (66.7%) who experienced thromboembolic complications had been poor responders to clopidogrel therapy in the initial P2Y12 inhibition test. The patient who experienced the hemorrhagic complication had become a hyper-responder to clopidogrel therapy after the initial P2Y12 inhibition test. There was a strong trend toward fewer perioperative complications in the second group of patients (6.7%) compared to the first (50%, p value 0.053). Conclusion: We found significant and dynamic variability in patient response to clopidogrel therapy in our initial cohort of patients treated with the Pipeline device, with 43% of patients falling outside the P2Y12 inhibition target therapeutic range in the perioperative period. This variability in patient response to clopidogrel therapy appears to be directly related to the perioperative thromboembolic and hemorrhagic complications in our cohort. Adopting a protocol with early initiation of dual antiplatelet therapy, rigorous pre and post-procedure P2Y12 inhibition testing, and active management of patients who fall outside the target therapeutic range may minimize the risk of perioperative thromboembolic and hemorrhagic complications in patients treated with the Pipeline device. Competing interests: J Delgado Almandoz: None. B Crandall: Covidien/ev3. J Scholz: None. J Fease: None. Y Kadkhodayan: None. R Anderson: None. D Tubman: Covidien/ev3.